2021
DOI: 10.3390/met12010020
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Graphene Oxide on the Regulations and Controls of the Sol-Gel Film Structure and Its Performance

Abstract: A facile strategy to boost anticorrosion potency of graphene oxide/silica hybrid sol-gel coating is developed through fully exploiting the capabilities of graphene oxide (GO). Together with a barrier to corrosives and crack inhibitor, GO was further explored herein as a regulator to regulate the gelation process and provide robust coating films with stratified microstructures and ultimately extended diffusion paths. The sol-gel coating with stratified microstructure achieved on AA5052 aluminum alloy surface af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The coating could effectively block the penetration of chloride ions to the surface of the Mg substrate, and significantly improve the corrosion resistance of the Mg alloy. Gao et al [116] used GO to modulate the sol-gel process to prepare sol-gel films with a layered structure. Sol particles were efficiently and densely cross-linked along the GO.…”
Section: Sol-gel/go Composite Coatingsmentioning
confidence: 99%
“…The coating could effectively block the penetration of chloride ions to the surface of the Mg substrate, and significantly improve the corrosion resistance of the Mg alloy. Gao et al [116] used GO to modulate the sol-gel process to prepare sol-gel films with a layered structure. Sol particles were efficiently and densely cross-linked along the GO.…”
Section: Sol-gel/go Composite Coatingsmentioning
confidence: 99%
“…Graphene oxide (GO) is a carbon-based nanomaterial characterized by different oxygen functional groups (such -OH and -COOH) on its basal planes and edges and has received a lot of attention in coating applications as its functional groups ensure its strong compatibility with matrices and additives. Additionally, GO has a great barrier property because of its high aspect-ratio flake-like structure [73]. The effects of GO-filled sol-gel sealing on the corrosion resistance and paint adhesion of anodized aluminum were investigated by Ye et al.…”
Section: Blue-growthmentioning
confidence: 99%
“…This type of material has unique characteristics that are easily recognizable (Huang et In the measured Raman spectrum (Fig. 2), it can be observed that there are two characteristic peaks located at 1359.23 cm -1 and 1592.57 cm -1 (Gao et al, 2021;Sun et al, 2019). Nano-carbon materials usually contain two obvious Raman peaks during research.…”
Section: Raman Spectrum Detectionmentioning
confidence: 99%